Poverty and Survival Prospects of Vietnamese Children under Doi Moi - Wagstaff, Adam (World Bank, Washington, D.C., 2013)
By international standards, and given its relatively low per capita income, Vietnam has achieved substantial reductions in, and low levels of, infant and under-five mortality. The authors review existing evidence and provide new evidence on whether, under the economic liberalization program known as Doi Moi, this reduction in child mortality has been sustained. They conclude that it has, but that the gains have been concentrated among the better-off. As a result, socioeconomic inequalities in child survival are evident in Vietnam-a change from the early 1990s when none were apparent. The authors develop survival models to find the causes of this differential decline in child mortality, and conclude that a number of factors have been at work, including reductions among the poor (but not among the better-off) in coverage of health services and in women's educational attainment. They argue that if the experience of the late 1990s is a guide to the future, the lack of progress among the poor will jeopardize Vietnam's chances of achieving the international development goals for child mortality. The authors examine various policy scenarios, including expanding coverage of health services, water and sanitation, and find that such measures, while useful, will have only a limited effect on the mortality of poor children. They find that programs aimed at narrowing the gap between the poor and better-off may have large beneficial effects on the various determinants of child survival.